Bamboo biochar addition enhanced cement mortar strength and CO2 sequestration ability - Jolius, Gimbun; Pravina K., Gunasekaran; Che, Jialing; Chin, Siew Choo (Elsevier Ltd, 2025)
This paper presents the enhancement of concrete strength and carbon dioxide sequestration through the addition of bamboo biochar. The effects of biochar addition on the compressive and flexural strength of cement mortar were optimized using response surface methodology. Biochar incorporation reduced the density of cement mortar and enhanced its water absorption capacity. The model predicted maximum compressive (35.27 MPa) and flexural strength (8.78 MPa) at 2.15 % biochar addition and a w/c ratio of 0.47. Experimental validation of the optimum point showed good agreement with the model predictions. The addition of bamboo biochar increased carbon dioxide sequestration by up to 18 % compared to the control sample. The sequestered CO2 formed carbonates within the cement mortar, enhancing compressive and flexural strength by up to 24 % and 9 %, respectively. The carbon footprint of cement mortar was reduced by up to 5.7 % with bamboo biochar addition. Furthermore, biochar addition decreased mortar density by 3 % and increased water absorption capacity by about 15 %. This study highlights the potential of bamboo biochar as an active filler in concrete, providing both structural benefits and improved carbon dioxide sequestration for sustainable construction. This advancement demonstrates promise for developing cementitious materials that contribute to carbon sequestration in the built environment.